Long-term outcomes and influencing factors following pediatric kidney transplantation: a single-center cohort study from China - Yu, Junhao; Sheng, Xiaoju; Li, Yuhong; Sui, Mingxing; Fu, Jiazhao; Zeng, Li; Li, Yanhua; Zhao, Wenyu (Frontiers in Pediatrics, 2025)
BackgroundKidney transplantation is recognized as the optimal treatment for end-stage kidney disease (ESKD) in children, which significantly improves growth delay, pubertal development, and social prognosis in pediatric patients. This study analyzed the long-term prognosis and influencing factors following pediatric kidney transplantation at our center.MethodsA total of 101 pediatric recipients who underwent kidney transplantation at our center were enrolled in this study. Post-transplant outcomes, including renal function, height development, pubertal progression, and social adaptation, were systematically analyzed.ResultsThe height-for-age Z-score (HAZ) significantly improved from −2.27 ± 1.64 at transplantation to −0.76 ± 1.13 after achieving post-transplant stability. The graft survival rates were 100% and 93.4% at 5 and 10 years post-transplantation, respectively, while patient survival rates remained 100% at both 5 and 10 years. At the last follow-up, the mean serum creatinine level was 83.85 ± 38.34 μmol/L, with an estimated glomerular filtration rate (eGFR) of 79.49 ± 27.25 ml/min/1.73 m2. Among school-aged recipients, 93.75% successfully returned to school, while only 33.3% of those who completed their education achieved employment. Among male adolescents (13 years, n = 43), 37 cases (86.0%) experienced spermarche, with a mean age of 14.5 years in prepubertal transplant recipients. In the female cohort (n = 45), 42 patients (12 years) reached puberty, demonstrating a mean menarche age of 12.5 years in prepubertal recipients vs. 13.2 years in postpubertal transplants (P > 0.05). Menstrual irregularities were observed in 8 cases, accounting for 19.51% of menstruating females.ConclusionThis study demonstrates significant improvements in height development, pubertal progression, and social adaptation following kidney transplantation in pediatric recipients. While recipient gender, pre-transplant dialysis modality, and dialysis duration showed no significant impact on near-final height (NFH), both transplantation age and height at transplantation significantly influenced NFH attainment. These findings emphasize that early transplantation and maintaining optimal graft function are crucial for ameliorating growth delay and pubertal development, while also positively influencing long-term social outcomes in pediatric transplant recipients.